The quality of tinuktuk in the frozen temperature storage - Marini Damanik; Ida Duma Riris; Nora Susanti; Nurul Ramadhaniyah; Jihan Afstria Rinanda (Pascasarjana Universitas Negeri Medan, 2024)
Tinuktuk is considered nutritious and able to boost immunity. A local product based on natural resources and spices in Indonesia. The different concentrations of the main ingredients used in the production of tinuktuk produce good quality and nutrition for safe, healthy, and nutritious consumption. So far, there is no optimum composition of tinuktuk and also quality analysis during the storage period in the frozen temperature of tinuktuk, so this research is necessary. In this research, the roasting method is used for the drying process of making tinuktuk. The roasting process is one of the isothermal drying processes. The purpose of this study was to determine the quality characteristics of tinuktuk during storage at -10°C for 56 days which is analyzed every 7 days. Tinuktuk characteristic parameters include pH, moisture content, ash content, and microbial analysis. The results of the research that have been carried out are 30%: 70% and 40%: 60%, which have similarities with the results of the analysis of tinuktuk that has been marketed, namely the 30%: 70% ratio, wherein the 30%: 70% ratio the pH analysis decreases steadily from 6.3 to 5.9. Ash content analysis resulted in a stable decrease from 7% to 5%. Microbial analysis with ALT testing resulted in stable data during storage at 2.5 x 102 colonies/g. Antioxidant analysis of 30%:70% ratio resulted in antioxidant IC50 data of 93, 4 ppm to 183.6 ppm.